Effects of Maize (Zea mays L.) Genotype at Different Planting Densities on Herbage Mass Productivity and Silage Chemical Composition - Kajol Somai; Mohan Mahato; Mahesh Regmi; Udit Prakash Sigdel; Dikshya Bist; Hari Kumar Shrestha; Abdu Rahman Beshir; Shanker Raj Barsila (International Journal of Agronomy)
Information regarding suitable maize (Zea mays L.) genotypes and plant density is needed for silage producers to produce high-quality silage. In the spring of 2022, a study was carried out to assess how different plant densities of maize hybrids affect the biomass yield and chemical composition of silage. The treatments were arranged in a split-plot design via a randomized completely block design with three replicates. The corresponding plant densities used as the main plots were 66,666 and 111,111 plants/ha (density). The maize genotypes included in the analysis as subplots were CAH–1715, RH–10, CAH–1511, RML–86/RML–96, CAH–196, and RML–95/RML–96. The maize was harvested and weighed for biomass yield and subsequently subjected to ensiling. A standard laboratory protocol was followed to evaluate the chemical composition of the ensiled maize genotypes. The results revealed that the energy content, pH, neutral detergent fiber (NDF), acid detergent fiber (ADF), and days to 50% tasseling and silking were all unaffected by genotype. The highest biomass (49.39 t/ha) and dry matter production (16.98 t/ha) were obtained for genotype CAH–1715. The crude protein (CP) content was greatest (9.86%) for the CAH–196 genotype. Similarly, different plant densities did not affect pH, energy, NDF, ADF, ear height, or plant height. The leaf area index, days to 50% tasseling and silking, biomass yield, and dry matter production significantly increased (p<0.05) with increasing plant density, whereas the leaf area per plant and CP decreased. These results indicated a decline in the nutritive quality of silage with increasing plant density. The study revealed that CAH–1715, with a plant density of 111,111 plants/ha, was suitable for making silage with a high biomass output, although a lower plant density might be suitable for silage of greater quality. However, silage quality is yet to be explored in detail.